Metaphors in the Lyrics of “Chandelier” by Sia - Salman Hasyim A; Otong Setiawan Djuharie (Indo Publishing, 2025)
The findings reveal four distinct types of metaphors employed in the song's lyrics: dead metaphors, creative metaphors, dormant metaphors, and implicit metaphors. For instance, the phrase